Analisis Informasi Keuangan dalam Mengevaluasi Kinerja Pemerintah Kabupaten Deli Serdang - Icce Leni Damanik; Mariyam (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to evaluate the performance of the Deli Serdang Regency government using ratio analysis; Independence Ratio, Regional Financial Dependency Ratio, Degree of Fiscal Decentralization Ratio, PAD Effectiveness Ratio, PAD Efficiency Ratio, Harmony Ratio. This research uses a descriptive quantitative analysis method with the research subject being a report on the realization of the Deli Serdang Regency government's budget and income for 2019-2023 using financial ratio analysis techniques. The research results show that the Regional Financial Independence Ratio shows an average percentage over the last five years of 37.93%, which is in the low criteria. The Dependency Ratio shows an average percentage over the last five years of 67.85%, which is in the medium criteria. The Degree of Fiscal Decentralization Ratio shows that the average percentage over the last five years was 25.74%, which is in the sufficient criteria. The PAD Effectiveness Ratio shows that from 2019 to 2023 it is not effective with an average percentage of 68.07%. The PAD Efficiency Ratio with an average percentage over the last five years of 1.46% is in the Very Efficient criteria. The Operating Expenditure Ratio in 2019 was 77.00%, in 2020 it was 80.25%, there was an increase of 3.25%, in 2021 it was 69.80%, there was a decrease of 10.45%. In 2022 and 2023 there will be an increase of 70.46% and 71.45%. Capital expenditure to total expenditure in 2019 was 22.80%. In 2020, it was 17.33%, there was a decrease of 5.47%. From 2021 to 2023 there will be a decrease of 1.28%.